Melatonin hormone as a therapeutic weapon against neurodegenerative diseases - Asefy, Zahra; Khusro, Ameer; Mammadova, Shakar; Hoseinnejhad, Sirus; Eftekhari, Aziz; Alghamdi, Saad; Dablool, Anas S.; Almehmadi, Mazen; Kazemi, Elham; Sahibzada, Muhammad Umar Khayam (Cellular and Molecular Biology, 2021)
Brain disorders such as Alzheimer’s and Parkinson’s disease (PD) are irreversible conditions with several cognitive problems, including learning disabilities, memory loss, movement abnormalities, and speech problems. These disorders are caused by a variety of factors, mainly due to the toxic pollutants-induced biochemical changes in protein production, uncontrolled neuronal electrical activity, and altered neurotransmitter levels. Oxidative stress and toxicity associated with the increased glutamate levels decreased acetylcholine levels, and brain inflammation is the main contributing factor. Melatonin hormone is considered one of the potent treatment approaches for neurodegenerative disorders. Melatonin is released from the pineal gland and has a critical role in brain function regulation. Membrane receptors, binding sites, and chemical interaction mediate hormonal actions having multiple phenotypic expressions. It acts as a neurodegenerative agent against some neurological disorders such as Alzheimer’s disease (AD), PD, depression, and migraines. Melatonin inhibits neurotoxic pollutants-induced Tau protein hyperphosphorylation, especially in AD. Other pivotal features of melatonin are its anti-inflammatory properties, which decrease pro-inflammatory cytokines expression and factors such as IL-8, IL-6, and TNF. Melatonin also reduces NO (an inflammation factor). In this review, we have highlighted the protective effects of melatonin, mainly spotlighting its neuroprotective mechanisms that will be beneficial to assess their effects in environmental pollution-induced neurodegenerative pathology.